2017
DOI: 10.1016/j.molcel.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of RNA Polymerase II Termination at Protein-Coding Genes

Abstract: At the end of protein-coding genes, RNA polymerase (Pol) II undergoes a concerted transition that involves 3'-processing of the pre-mRNA and transcription termination. Here, we present a genome-wide analysis of the 3'-transition in budding yeast. We find that the 3'-transition globally requires the Pol II elongation factor Spt5 and factors involved in the recognition of the polyadenylation (pA) site and in endonucleolytic RNA cleavage. Pol II release from DNA occurs in a narrow termination window downstream of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
138
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 86 publications
13
138
0
Order By: Relevance
“…At the same time, because XRN2 inactivation does not fully prevent but only delays termination in human cells and because Rat1p depletion in yeast caused globally less severe termination defects than depletion of CPFs, alternative termination mechanisms have been speculated to compensate partially for loss of XRN2 (Fong et al 2015;Baejen et al 2017). Here, we provide direct evidence for the operation of an XRN2-independent pathway of transcriptional termination in Caenorhabditis elegans.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…At the same time, because XRN2 inactivation does not fully prevent but only delays termination in human cells and because Rat1p depletion in yeast caused globally less severe termination defects than depletion of CPFs, alternative termination mechanisms have been speculated to compensate partially for loss of XRN2 (Fong et al 2015;Baejen et al 2017). Here, we provide direct evidence for the operation of an XRN2-independent pathway of transcriptional termination in Caenorhabditis elegans.…”
mentioning
confidence: 71%
“…Since recent studies revealed that loss of XRN2/Rat1p activities caused global termination defects in yeast and human cells (Fong et al 2015;Baejen et al 2017), it seems possible that termination in C. elegans might differ from that in previously studied systems. For instance, termination on genes with fast elongation rates requires distances of several kilobases past pA signal in human cells (Fong et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its homolog, Rat1, was simultaneously found to promote termination more widely in budding yeast (Kim et al 2004), with recent transcriptome-wide analysis supporting this finding (Baejen et al 2017). The broader role of Xrn2 in human cells has been less clear.…”
mentioning
confidence: 99%
“…RNA interference (RNAi) of the human 5ʹ-3ʹ exonuclease, Xrn2, or mutation of its budding yeast equivalent, Rat1, was originally shown to disrupt termination on transfected plasmids and endogenous genes respectively [6,7]. Although the role of Rat1 was recently re-affirmed [8], RNAi of Xrn2 did not reveal a general termination defect at the 3ʹ end of protein-coding genes [9]. However, termination was subsequently shown to be affected when a catalytically inactive version of Xrn2 is expressed in an RNAi background [10].…”
Section: Overviewmentioning
confidence: 99%